Gambaran Morfologi Eritrosit Mahasiswi saat Menstruasi - Muhammad Syamsul Arif Setiyo Negoro; Glori Septilia (Jaringan Laboratorium Medis, 2024)
College students when entering the early adult phase have experienced puberty which is marked by menstruation. The duration of menstruation between one woman and another varies greatly so that the volume of blood released also varies. Excessive blood loss can reduce iron (Fe) levels in the body of female students and can affect erythrocyte morphology. Researchers conducted this study with the aim of knowing the description of erythrocyte morphology of female college students during menstruation. The research conducted is included in the type of descriptive research with observational design. The population was d3 TLM class 12 students with a sample size of 20 students who were experiencing menstruation. The sampling technique used incidental sampling. The results described the morphology of erythrocytes in female students of DIII Medical Laboratory Technology Batch XII Poltekkes Kemenkes Semarang during menstruation on the 4th day based on aspects of assessment of erythrocyte size, namely 7 people (35%) included in the microcytic category and 13 people (65%) included in the normocytic category. Based on the aspect of erythrocyte staining, 7 people (35%) were included in the hypochromic category and 13 people (65%) were included in the normochromic category. While based on the aspect of assessing the shape of erythrocytes, all 20 respondents (100%) were included in the mild poikilocytosis category. The conclusion that can be drawn from this study is the picture of erythrocyte morphology of DIII Medical Laboratory Technology Batch XII Poltekkes Kemenkes Semarang students during menstruation on the 4th day, out of 20 respondents as many as 7 people (35%) showed hypochromic microcytic erythrocyte morphological abnormalities with mild poikilocytosis and 13 people (65%) showed normocytic normochromic erythrocyte morphological abnormalities with mild poikilocytosis. It is recommended to increase the consumption of vegetables and foods that increase the formation of red blood cells during menstruation.